Optimal planting pattern of cotton is regulated by irrigation amount under mulch drip irrigation - Zuo, Wenqing; Wu, Baojian; Wang, Yuxuan; Xu, Shouzhen; Tian, Jingshan; Jiu, Xingli; Dong, Hengyi; Zhang, Wangfeng (Frontiers in Plant Science, 2023)
It is of great importance to explore agronomic management measures for water conservation and cotton yield in arid areas. A four–year field experiment was conducted to evaluate cotton yield and soil water consumption under four row spacing configurations (high/low density with 66+10 cm wide, narrow row spacing, RS66+10H and RS66+10L; high/low density with 76 cm equal row spacing, RS76H and RS76L) and two irrigation amounts (CI: conventional drip irrigation; LI: limited drip irrigation) during the growing seasons in Shihezi, Xinjiang. A quadratic relationship was observed between the maximum LAI (LAImax) and seed yield. Canopy apparent transpiration rate (CAT), daily water consumption intensity (DWCI) and crop evapotranspiration (ETC) were positively and linearly correlated with LAI. The seed yields, lint yields, and ETC under CI were 6.6–18.3%, 7.1–20.8% and 22.9–32.6% higher than those observed under LI, respectively. The RS66+10H under CI had the highest seed and lint yields. RS76L had an optimum LAImax range, which ensured a higher canopy apparent photosynthesis and daily dry matter accumulation and reached the same yield level as RS66+10H; however, soil water consumption in RS76L was reduced ETC by 51–60 mm at a depth of 20–60 cm at a radius of 19–38 cm from the cotton row, and water use efficiency increased by 5.6–8.3% compared to RS66+10H under CI. A 5.0< LAImax < 5.5 is optimum for cotton production in northern Xinjiang, and RS76L under CI is recommended for high yield and can further reduce water consumption. Under LI, the seed and lint yields of RS66+10H were 3.7–6.0% and 4.6–6.9% higher than those of RS76L, respectively. In addition, high-density planting can exploit the potential of soil water to increase cotton yields under water shortage conditions.